Strategic mapping of onion supply chains: a comprehensive analysis of production and post-harvest processes in Northwest Ethiopia - Yeshiwas, Yebirzaf; Alemayehu, Melkamu; Adgo, Enyew (Frontiers in Sustainability, 2024)
Introduction Onion is a significant vegetable crop in Ethiopia, serving as a source of income for smallholder farmers. However, various challenges in the production and post-harvest handling processes impede a consistent supply and marketing of the crop. This study focused on a comprehensive analysis of the onion supply chain, ranging from production to post-harvest handling, to address the existing production and marketing processes. The research initiative was undertaken to map the onion supply chain from farmers to consumers, intending to establish an improved marketing system in northwest Ethiopia. Methods The study area covered three onion-producing districts of the Amhara Region. Data collection involved interviews, observations, and market assessments using a structured questionnaire. Sampling followed a multistage technique. The analysis included descriptive statistics and food system analysis to map the supply chain and estimate marketing margins. Results and Discussion Post-harvest loss in onion production presents a major obstacle in the farming sector, impacting its growth. The study identified six alternative channels for onion marketing where different actors are involved throughout the supply chain. Key stakeholders include farmers, local collectors, brokers, transporters, wholesalers, retailers, and consumers. Packaging and sorting activities are implemented at different supply chain stages to minimize post-harvest losses. Farm-level activities, including curing, sorting, grading, and ventilating, are crucial for reducing losses. The perishable nature of onion bulbs and the existing production and handling challenges exacerbate post-harvest losses. Efforts to address this challenge demand a comprehensive approach, integrating interventions across the value chain, from improved cultivars and storage infrastructure to enhanced market access strategies. Hence, stakeholders and governmental organizations are urged to promote onion value-addition technologies, including the establishment of processing industries. Such endeavors promote collaborative efforts across the onion supply chain, ensuring sustainable benefits for producers and traders.